Science - Taavitsainen, Irma; Landert, Daniela (A new companion to Chaucer, 2019)
This chapter gives an overview of the presence of science in Chaucer's writing. Chaucer's work includes several texts and passages that deal with science explicitly. In addition, science plays a role in many texts implicitly by affecting the mood of the texts. The chapter includes an outline of the socio-historical background of scientific writing in Chaucer's time, covering various branches of science as understood in the late-medieval period. An analysis of selected passages of Chaucer's texts shows how they reflect the scientific ideas of his time and how Chaucer made use of scientific references for describing events and characters.
Gesehen am 04.04.2024